Conservação de alimentos : uma sequência didática interativa na perspectiva CTSA - Leite, Eliane Glerian (2018)
In the teaching action, it is necessary to explore activities closer to the reality of the student, valuing their daily life and promoting the possibility of a more meaningful and more collaborative learning. It is necessary to stimulate the student's curiosity in understanding the concepts, highlighting the role of this reality through a contextualization in the perspective of Science, Technology and Society, taking into account their environment (CTSA). Exploring and stimulating are challenges that present themselves to Science / Chemistry teaching that can, among other things, enable students to take a scientific reading of phenomena and material transformations. The path adopted in this work was to value the students' experiences using the previous knowledge in class planning in the CTSA perspective. Teaching strategies can promote a greater interaction between the subjects of learning as a way to facilitate the understanding of nature from the scientific culture, besides contributing to a critical formation and of conscious positioning before the problems. In this research, an interactive didactic sequence (SDI) was elaborated from the theme: Food conservation. As a structural question we choose this: How do students understand the phenomena related to food conservation, from the application of a SDI in the CTSA perspective? Five classes were planned and applied, including two experimental ones, from what the students knew about the browning of the apple and ways to avoid the rotting of some foods. This research report is structured in seven chapters as follows: In the first chapter, the researcher's academic and professional background is presented. The second chapter discusses the problem, the objectives and the methodology adopted. In the third chapter, we discuss the composition of the acronym CTS and its variant for CTSA, as well as on the strengthening of questions and environmental concepts in the most current scientific education. The fourth chapter discusses SDI and how interactivity can value students' realities. In the fifth chapter, the teaching about food preservation and the concepts of chemical kinetics involved in the process are discussed, as well as the relevance of the understanding of this subject in the context of high school. The sixth chapter, especially discusses the didactic guide, as a developed educational product. Several topics and concepts were mentioned by the students, such as: to use or not the refrigerator, consumption of milk and fresh meat, use of oil (as in canned meat) and salt to preserve, choose the best way to store ( packaging, canning, conditioning) and preserving food, the concepts of temperature, time and contact surface, were indications of the richness provided by the possibility of a more systematic application of the CTSA perspective from the chosen theme. To elaborate and apply a SDI are possible actions, however, the actual conditions of teaching performance, as well as the systematization of student learning, seem to be the most degrading obstacles to its full realization.